1996
DOI: 10.1093/oxfordjournals.annonc.a010802
|View full text |Cite
|
Sign up to set email alerts
|

Activity of single agent vinorelbine in pretreated non-Hodgkin's lymphoma

Abstract: The good activity and tolerability of vinorelbine in relapsed intermediate-high grade lymphoma suggest its inclusion in first-line regimens, especially in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…21 Studies have documented the antilymphoma activity of vinorelbine in both low grade and aggressive NHL when used in the relapsed setting. 22 Rituximab is an anti-CD20 monoclonal antibody approved for the treatment of indolent NHL, with demonstrated activity in a wide spectrum of B-cell malignancies. [23][24] Due to nonoverlapping toxicity and to possible additive or synergistic effects, rituximab is routinely used in combination with chemotherapeutic agents with encouraging results.…”
Section: Introductionmentioning
confidence: 99%
“…21 Studies have documented the antilymphoma activity of vinorelbine in both low grade and aggressive NHL when used in the relapsed setting. 22 Rituximab is an anti-CD20 monoclonal antibody approved for the treatment of indolent NHL, with demonstrated activity in a wide spectrum of B-cell malignancies. [23][24] Due to nonoverlapping toxicity and to possible additive or synergistic effects, rituximab is routinely used in combination with chemotherapeutic agents with encouraging results.…”
Section: Introductionmentioning
confidence: 99%
“…3 In phase I studies in humans, the doselimiting toxicity was neutropenia, with minimal nonhematologic toxicities observed. 3,4 In phase II clinical trials in humans, use of vinorelbine revealed activity against lung, 5 breast, 6 ovarian, 7 and head and neck 8 cancers in addition to non-Hodgkin's lymphoma, 9 Karposi sarcoma, 10 and mesothelioma. 11 Other toxicities that have been reported in humans are peripheral neuropathy, 12 pain at the tumor site after vinorelbine injection, 13 rare acute cardiopulmonary toxicity, 14 and skin necrosis if extravasated.…”
mentioning
confidence: 99%
“…In the patients with HD a response rate of 50 per cent was seen, compared with 44 per cent in NHL: results that are broadly in line with previous phase II single agent studies. 10,11,14 We used a less intense schedule of vinorelbine than had been used previously, and less than 5 per cent of scheduled drug administration was delayed (6 out of 132 injections) compared with the 67-80 per cent with a schedule of 30 mg/m 2 per week. The therapy was generally well-tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…Responses in up to 50 per cent of patients with both relapsed refractory NHL and heavily pre-treated HD occur when vinorelbine is employed as a single agent, with some complete responses seen in both groups. 10,11 Since the majority of patients with relapsed HD and NHL will ultimately die of their disease and many are not eligible for high-dose treatments, new agents are required. We report the results of a phase II study employing single agent vinorelbine as a salvage treatment in patients with NHL and HD, half of whom had received prior high-dose therapy.…”
Section: Introductionmentioning
confidence: 99%